Nonlinear Response of Strong Nonlinear System Arisen in Polymer Cushion. (5th February 2013) - Wang, Jun; Lu, Li-xin; Jiang, Huan-xin; Zhu, Yong
Abstract : A dynamic model is proposed for a polymer foam-based nonlinear cushioning system. An accurate analytical solution for the nonlinear free vibration of the system is derived by applying He's variational iteration method, and conditions for resonance are obtained, which should be avoided in the cushioning design.